Eight Years of Severe Allergic Reactions in Finland: A Register-Based Report - Mäkinen-Kiljunen, Soili (World Allergy Organization, 2008)
BACKGROUND: No data have been available on severe allergic reactions in Finland. MATERIALS AND METHODS: We summarize the data accumulated from 2000 to 2007 in the national register established at the Skin and Allergy Hospital of the Helsinki University Central Hospital, where physicians voluntarily report on patients with severe allergic reactions. RESULTS: During the period, the 530 reported cases of severe allergic reactions represented an annual frequency of 0.001%. Of the patients, 66% were adults and 56% were female, with a median age of 27 years. Food was the causative agent in 53% of the cases, drugs in 26%, allergen preparations in 12%, and insects in 8%. Dermatologic symptoms were reported in 85%, respiratory in 76%, cardiovascular in 50%, gastrointestinal in 33%, and eye/nose symptoms in 18%. The reaction was a life-threatening anaphylactic shock in 26% of the cases, with no deaths reported. Patients were treated with intramuscular adrenaline in 75% of the cases. Not only nuts and seeds, but also fruit and vegetables were the most important allergens for the adults. Nuts were also important allergens for children, along with milk, egg, and wheat. In addition, many "exotic" allergens were identified: patent blue, carmine dye, yeast, buckwheat, and macrogol. CONCLUSIONS: Severe allergic reactions are underreported, but a register reflects the real-life situation and helps to identify new causative agents. It also contributes to improvements in first aid treatment practice.